Engineering Software Solution for Thermal Elastohydrodynamic Lubrication Using Multiphysics Software. (1st February 2016) - Lohner, Thomas; Ziegltrum, Andreas; Stemplinger, Johann-Paul; Stahl, Karsten
Abstract : The complexity of thermal elastohydrodynamic lubrication (TEHL) problems has led to a variety of specialised numerical approaches ranging from finite difference based direct and inverse iterative methods such as Multilevel Multi-Integration solvers, via differential deflection methods, to finite element based full-system approaches. Hence, not only knowledge of the physical and technical relationships but also knowledge of the numerical procedures and solvers is necessary to perform TEHL simulations. Considering the state of the art of multiphysics software, the authors note the absence of a commercial software package for solving TEHL problems embedded in larger multiphysics software. By providing guidelines on how to implement a TEHL simulation model in commercial multiphysics software, the authors want to stimulate the research in computational tribology, so that, hopefully, the research focus can be shifted even more on physical modelling instead of numerical modelling. Validations, as well as result examples of the suggested TEHL model by means of simulated coefficients of friction, coated surfaces, and nonsmooth surfaces, highlight the flexibility and simplicity of the presented approach.